2003
DOI: 10.1097/00001432-200304000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcal resistance revisited: community-acquired methicillin resistant Staphylococcus aureus - an emerging problem for the management of skin and soft tissue infections

Abstract: More local data on CA-MRSA infections are needed so that dermatologists and community physicians can assess the risk of such infections amongst their patients and avoid the inappropriate administration of beta-lactams. No simple change in prescribing practices will entirely alleviate selective pressure for the spread of community-acquired MRSA and not exacerbate resistance in pyogenic streptococci, commonly found together with S. aureus in skin and soft tissue infections. The importance of hygiene in preventin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
188
2
11

Year Published

2004
2004
2013
2013

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 301 publications
(214 citation statements)
references
References 123 publications
6
188
2
11
Order By: Relevance
“…It is predominantly associated with skin and soft tissue infections (especially abscesses and cellulitis). When present, risk factors are generally similar to those for infection with MSSA [28]. Some CA-MRSA strains have entered the hospital environment and caused outbreaks of infection, which has led to difficulty in distinguishing these strains from traditional nosocomial ones.…”
Section: Discussionmentioning
confidence: 99%
“…It is predominantly associated with skin and soft tissue infections (especially abscesses and cellulitis). When present, risk factors are generally similar to those for infection with MSSA [28]. Some CA-MRSA strains have entered the hospital environment and caused outbreaks of infection, which has led to difficulty in distinguishing these strains from traditional nosocomial ones.…”
Section: Discussionmentioning
confidence: 99%
“…PVL has not yet been found in pig-associated strains (Huijsdens et al, 2006), but more studies need to be conducted to confirm this. There are relatively few CA-MRSA strains, with 6 currently recognised (Eady and Cove, 2003). It has been suggested that these strains are associated with particular niches (Shukla, 2005), concurring with the potential association of the above sequence types with pigs and pig farmers.…”
Section: B Environmental Reservoirs Of Mrsamentioning
confidence: 93%
“…Al- Figure 1. Algorithm 1, part 1: approach to treating a diabetic patient with a foot wound though MRSA strains have previously been isolated mainly from hospitalized patients, community-associated cases are now becoming common [45] and are associated with worse outcomes in patients with diabetic foot infections [46][47][48]. Vancomycin (or glycopeptide)-intermediate S. aureus has been isolated in several countries.…”
Section: Microbiologymentioning
confidence: 99%